Power and prowess reexamine the ESSCOM operation in ESSZONE / Mohd Nazri Douglas and Mohd Israfil Mohd Fadzil - Douglas, Mohd Nazri; Mohd Fadzil, Mohd Israfil (2016)
This study was conducted to examine the role of Eastern Sabah Security Command (ESSCOM ) in protecting Sabah from the internal and external threats especially coping with the illegal immigrants that become a major issues and political issues since the middle of seventies. Other than that, this study also will identify specifically the programmes operation that been conducted by ESSCOM since its establishment after the incident happened in Kampung Tanduo, Lahad Datu Sabah in 2013. The time frame of this research is began from the establishment of ESSCOM in 2013 to the present. Federal government's actions through this agency were analyzed to determine whether actions taken are effective in addressing the issues that happened not only inside of Sabah but also around the waters border between Malaysia and Philippines because the following trends of threats is more on cross border crime where is the group from the Southern of Philippines actively seeking for KFR (Kidnap For Ransom). Throughout the years from 2013 until present, there are a lot of cases pertaining kidnapping that happened in our borders that will be explained in the problem statement later on. As long as this case continuously to be happened, it will give a bad impact towards the tourism site in the eastern part and also the safety of Sabahan people. Other than that, people now questioning the effectiveness of ESSCOM in preventing the terrorism threats since a lot of Malaysian people has been kidnapped but there is no a clear SOP by government in term of negotiating and combating this criminal. Illegal immigrants considered as a threat as contributing to the cross border crime happened our waters since some group of this migrants has a connection with the group in the southern of Philippines who belief as an 'insider' who are giving information towards the modus operandi and operation on how our security enforcers securing our borders from outside threats. The unwillingness of Philippines government in addressing this issue, the complexity of these illegal immigrations in Sabah has contributing to a lot of problems.